Characterizing the inhibition of α‐synuclein oligomerization by a pharmacological chaperone that prevents prion formation by the protein PrP. (2nd August 2019) - Dong, Chunhua; Garen, Craig R.; Mercier, Pascal; Petersen, Nils O.; Woodside, Michael T.
Abstract: Aggregation of the disordered protein α‐synuclein into amyloid fibrils is a central feature of synucleinopathies, neurodegenerative disorders that include Parkinson's disease. Small, pre‐fibrillar oligomers of misfolded α‐synuclein are thought to be the key toxic entities, and α‐synuclein misfolding can propagate in a prion‐like way. We explored whether a compound with anti‐prion activity that can bind to unfolded parts of the protein PrP, the cyclic tetrapyrrole Fe‐TMPyP, was also active against α‐synuclein aggregation. Observing the initial stages of aggregation via fluorescence cross‐correlation spectroscopy, we found that Fe‐TMPyP inhibited small oligomer formation in a dose‐dependent manner. Fe‐TMPyP also inhibited the formation of mature amyloid fibrils in vitro, as detected by thioflavin T fluorescence. Isothermal titration calorimetry indicated Fe‐TMPyP bound to monomeric α‐synuclein with a stoichiometry of 2, and two‐dimensional heteronuclear single quantum coherence NMR spectra revealed significant interactions between Fe‐TMPyP and the C‐terminus of the protein. These results suggest commonalities among aggregation mechanisms for α‐synuclein and the prion protein may exist that can be exploited as therapeutic targets.